Real-Life Experience of Hepatitis C Treatment with Direct-Acting Antivirals in Genotypes 2 and 3 - Kaya, Sibel Yıldız; Kurtaran, Behice; Öztoprak Çuvalcı, Nefise; Önlen, Yusuf; Ceylan, Mehmet Reşat; Zerdali, Esra; Sarı, Nagehan Didem; Öncül, Ahsen; Erben, Nurettin; Batirel, Ayse; et al. (Turkish Journal of Gastroenterology, 2025)
Background/Aims: This study evaluates the efficacy and safety of direct-acting antivirals (DAAs) in treating hepatitis C virus (HCV) genotype 2 (GT-2) and genotype 3 (GT-3) in Türkiye. Materials and Methods: This cohort is a multicenter, retrospective, and observational study. Data from 267 GT-2 or GT-3 patients treated with a DAA were analyzed. Results: An overall sustained virological response (SVR) rate of 95.9%, with no significant difference between GTs. The SVR rates were relatively lower in patients with cirrhosis. Prior pegylated interferon and ribavirin reduced SVR rates, particularly in males and patients with cirrhosis. The most common treatments were sofosbuvir-based regimens, which demonstrated comparable efficacy. No significant drug interactions were observed. The most commonly reported adverse events were fatigue and mild anemia, particularly in cirrhotic patients; however, these did not lead to treatment discontinuation. Conclusion: This study supports the efficacy and tolerability of DAA regimens for these HCV GTs, thereby reinforcing their role in HCV eradication. Cite this article as: Kaya SY, Kurtaran B, Çuvalcı NÖ, et al. Real-life experience of hepatitis C treatment with direct-acting antivirals in genotypes 2 and 3. Turk J Gastroenterol. Published online September 10, 2025. doi: 10.5152/tjg.2025.24751.